2005
DOI: 10.4049/jimmunol.174.1.485
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Is a Critical Effector and a Target for Therapy in Antiphospholipid Antibody-Induced Pregnancy Loss

Abstract: The antiphospholipid syndrome (APS) is characterized by recurrent fetal loss, intrauterine growth restriction, and vascular thrombosis in the presence of antiphospholipid (aPL) Abs. Our studies in a murine model of APS induced by passive transfer of human aPL Abs have shown that activation of complement and recruitment of neutrophils into decidua are required for fetal loss, and emphasize the importance of inflammation in aPL Ab-induced pregnancy loss. In this study, we examine the role of TNF-α in pregnancy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
154
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 213 publications
(164 citation statements)
references
References 51 publications
4
154
2
4
Order By: Relevance
“…It has been suggested that TNF-a plays an important role in inducing APS-related pregnancy loss [30], and thrombosis [12,31]. However, in our study, we were unable to find any significant differences in TNF-a levels between patients with and without APS clinical symptoms.…”
Section: Discussioncontrasting
confidence: 91%
“…It has been suggested that TNF-a plays an important role in inducing APS-related pregnancy loss [30], and thrombosis [12,31]. However, in our study, we were unable to find any significant differences in TNF-a levels between patients with and without APS clinical symptoms.…”
Section: Discussioncontrasting
confidence: 91%
“…These observations suggest that activation of the complement cascade contributes to the pathogenic effects of aPLA, most likely via the capacity of C5a in placental tissues to attract and activate immune cells and to stimulate the release of inflammatory mediators, including TNF-α [19][20][21].…”
Section: Cell Activation By Aplamentioning
confidence: 98%
“…Of considerable interest is the very recent finding that aPL antibodies appear to induce the expression of TNFα in decidual tissues [28]. This activity appears to occur downstream of complement activation.…”
Section: Preeclampsia: An Immune Disorder?mentioning
confidence: 99%
“…As TNFα has been shown to be very deleterious to fetal and placental tissues [29] and leads to fetal loss in pregnant mice, this could be a further explanation for the pathology of aPL antibodies in RFL. On the basis of these data, it has been suggested that anti-TNFα therapy may be useful for treating patients with RFL due to aPL antibodies [28].…”
Section: Preeclampsia: An Immune Disorder?mentioning
confidence: 99%
See 1 more Smart Citation